ON THE EXPERIENCE OF TIME IN CHARLES OF ORLEANS (Filološke pripombe, 2019)
The poetic persona of Charles of Orleans, one of the foremost French poets of the XVth century, is markedly determined by nostalgia, a specifically time-related kind of melancholy which his poetry is permeated with even more than that of his contemporary Alain Chartier. The expression of this disposition of mind and spirit seems more lucid in the poems of the Duke of Orleans than in any poetic corpus of the time.